Characterization of the foreign body response of titanium implants modified with polyphenolic coatings. Issue 7 (26th February 2022) - Weber, Florian; Quach, Huy Quang; Reiersen, Mathias; Sarraj, Sadaf Yosef; Bakir, Dyala Nidal; Jankowski, Victor Aleksander; Nilsson, Per H.; Tiainen, Hanna
Abstract: The foreign body response is dictating the outcome of wound healing around any implanted materials. Patients who suffer from chronic inflammatory diseases and impaired wound healing often face a higher risk for implant failure. Therefore, functional surfaces need to be developed to improve tissue integration. For this purpose, we evaluated the impact of surface coatings made of antioxidant polyphenolic molecules tannic acid (TA) and pyrogallol (PG) on the host response in human blood. Our results showed that although the polyphenolic surface modifications impact the initial blood protein adsorption compared to Ti, the complement and coagulation systems are triggered. Despite complement activation, monocytes and granulocytes remained inactivated, which was manifested in a low pro‐inflammatory cytokine expression. Under oxidative stress, both coatings were able to reduce intracellular reactive oxygen species in human gingival fibroblasts (hGFs). However, no anti‐inflammatory effects of polyphenolic coatings could be verified in hGFs stimulated with lipopolysaccharide and IL‐1β. Although polyphenols reportedly inhibit the NF‐κB signaling pathway, phosphorylation of NF‐κB p65 was observed. In conclusion, our results indicated that TA and PG coatings improved the hemocompatibility of titanium surfaces and have the potential to reduce oxidative stress during wound healing.